Nutritional Quality, Fodder Value and Regeneration Potential of Helecteres isora Linn - Bhatt, A. B.; Rawat, Neelam; Chandola, Amol (Indian Forester, 1992)
Tbe nutritional qualities of Helecteres isora Linn., a shrub with good coppicing ability were assessed along with palatability, phenological stages and regeneration potential. The findings indicated that the species can be used as a promising fodder plant in the hills specially at low elevations.